(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: The study aims to describe the situation of nasal-sinus diseases among outpatient patients visiting Viet Tiep Friendship Hospital, Hai Phong city in 2024. Research methods: A retrospective descriptive study included all subjects diagnosed with nasal-sinus diseases who had complete medical records. Data were retrieved from the electronic medical record system at Viet Tiep Friendship Hospital from January to December 2024. Results: Out of a total of 4140 patient visits to the otorhinolaryngology clinic of Viet Tiep Friendship Hospital, 47.8% were diagnosed with nasal-sinus diseases. Chronic rhinitis (J31.1) was the most commonly diagnosed condition, accounting for 80.2% of cases. The highest number of patient visits occurred in March and June. Female patients constituted 54% of visits, while male patients accounted for 46%, with the majority being patients over 60 years old (27.5%). Conclusions: Nasal-sinus diseases are the most common conditions among patients visiting the otorhinolaryngology clinic, with chronic rhinitis being the predominant diagnosis. The peak periods for patient visits were in March and June, and the majority of patients were over 60 years old.